Integration of physico-chemical and enzymatic pretreatments of oil palm biomass for enhancement of glucose production - Ahmad Rizal, Nur Fatin Athirah (2018)
Oil palm empty fruit bunch (OPEFB) and oil palm mesocarp fiber (OPMF) are lignocellulosic biomass that abundantly generated in palm oil mills. However, the presence of these oil palm wastes has created a major disposal problem. Current treatment is either by mulching at the plantation of dumping at side of the mill. Since these materials are rich in carbohydrate the OPEFB and OPMF have been widely reported as suitable raw materials to produce fermentable sugars. However, the presence of lignin and hemicellulose in their composition hinders the access of cellulase to hydrolyze cellulose. Effective pretreatments are required to reduce the recalcitrance of lignocellulosic structures and improve the fermentable sugars production. Combination of physico-chemical and biological pretreatment was proposed to enhance glucose production from OPEFB and OPMF. Physico-chemical pretreatment using superheated steam (SHS) was employed in this study as it can modify the lignocellulosic materials. Results showed SHS pretreatment alone had increased the percentage of cellulose by 13.4% for OPEFB and 19.4% for OPMF, and reduced hemicelluloses percentage to 18.7% and 21.3%, respectively. However, this SHS pretreatment could only generated 18.4% of glucose yield for OPEFB and 15.6% for OPMF. In order to enhance the glucose yield, combination pretreatments of SHS with laccase has been studied. Study showed that the best laccase loading for OPEFB was 100 U/g-substrate while for OPMF was 400 U/g-substrate. This raw size SHS + laccase pretreatment had enhanced 34.6% and 36.1% of glucose yield for OPEFB and OPMF, respectively. The delignification of OPEFB and OPMF was further improved by reducing the particle size to 2 mm, 1 mm, 0.5 mm and 0.25mm using a hammer mill after the SHS pretreatment and before treating with laccase. The reduction of size to 0.25 mm had improved the glucose yield by 71.5% for OPEFB and 63.0% for OPMF which is equivalent to 4.6-fold and 4.8- fold increment, respectively as compared to untreated substrates. To conclude, this study revealed that glucose yield was successfully enhanced by combining SHS with laccase pretreatment together with the size reduction of OPEFB and OPMF.